Implementation of the Islamic Economics in the Traditional Market of Brebes Regency - Akbar Nuur Purnama Darma Wahana; Muhammad Syaifulloh (Journal of Social Science, 2020)
The concept of Islamic Economics emphasizes that market Trading and pricing need to be regulated to uphold market balance and economic justice in view of interests of those involved in the market. This study aims to analyze the Islamic Economy’s observance in accordance with Islamic sharia in the traditional markets, the number of merchant populations used as samples was 138 people, the research method uses qualitative descriptive, data collection techniques by observation and structured interviews. The results showed that traders in the traditional market of Manis Kosambi Cikakak Village had practiced trade with Islamic Business Ethics. The Practice of Islamic Economy in the Traditional Market of Brebes Regency had been carried out by most traders almost 84.8%. The system of commerce with the islamic economy is rooted in and habutual practices with islamic business ethics, doing bussiness by selling clean products, honesty, openness, fair, and by backing out of riba, or loan shark has been accustomed by traditional merchants of Brebes Regency in Manis Kosambi market Cikakak Village of Brebes Regency Keywords: Islamic Economic Traditional Market